Seeking Impact and Visibility - Trotter, Henry,Kell, Catherine,Willmers, Michelle,Gray, Eve,King, Thomas (African Minds, 2014)
African scholarly research is relatively invisible globally because even though research production on the continent is growing in absolute terms, it is falling in comparative terms. In addition, traditional metrics of visibility, such as the Impact Factor, fail to make legible all African scholarly production. Many African universities also do not take a strategic approach to scholarly communication to broaden the reach of their scholars'work. To address this challenge, the Scholarly Communication in Africa Programme (SCAP) was established to help raise the visibility of African scholarship by mapping current research and communication practices in Southern African universities and by recommending and piloting technical and administrative innovations based on open access dissemination principles. To do this, SCAP conducted extensive research in four faculties at the Universities of Botswana, Cape Town, Mauritius and Namibia.To address this challenge, the Scholarly Communication in Africa Programme (SCAP) was established to help raise the visibility of African scholarship by mapping current research and communication practices in Southern African universities and by recommending and piloting technical and administrative innovations based on open access dissemination principles. To do this, SCAP conducted extensive research in four faculties at the Universities of Botswana, Cape Town, Mauritius and Namibia.
Keywords: scholarly communication; research; publishing; impact; visibility; Wissenschaftliche Literatur; Open Access; Universität; Einfluss; Sichtbarkeit; Communication studies; Higher & further education; tertiary education; Colleges of higher education